Pilot study on conservation of animal genetic resources - Food and Agriculture Organization of the United Nations; United Nations Environment Programme (Food and Agriculture Organization of the United Nations, 1975)
Project report on the conservation of animal genetic resources. Remedies for conservation of domestic breeds in danger of extinction, as well as animal genetic resources in general are proposed. Annexes on comparisons of the breed situation in Corsica and Sardinia in cattle, sheep, goats, pigs and equidae; disappearing cattle breeds in Europe and the Mediterranean basin included. Preliminary survey of endangered breeds throughout the world, the mission on the Kuri cattle of lake Chad including various other contacts made within the scope of the project also reported.